Pengaruh Pengembangan Sumber Daya Manusia dan Kompetensi Karyawan terhadap Kinerja Karyawan di Hotel Niagara Parapat Toba Sumatera Utara - Weddy Nur Adam; Wan Suryani; Eka Setia Dewi Tarigan (Jurnal Ilmiah Manajemen dan Bisnis (JIMBI), 2021)
This research aims to know "the influence of human resources development and competence on the performance of Hotel Niagara Parapat employees". This type of research is associative which is a research that is asking relations between two variables. The population in this study was the Hotel employee of Niagara Parapat, as many as 155 employees. And by using slovin formula, the number of samples in this study was as much as 61 respondents taken from all employees of the population. Based on the test results it can be seen that the partial test on the development of human Resources variable (X1) and the competency variable (X2) partially have a positive and significant influence on the performance variable (Y). Based on the test results F obtained the development of human Resources (X1) and competence (X2) simultaneously influence positively and significantly against the performance variables. And can be deduced from the Adjusted R Square value obtained by 0.679. To see the great effect of free variables against variables bound by calculating coefficient of determination (KD) = R2 x 100%, so it is obtained by 67.9%. Performance (bound variables) can be explained by the development of human Resources (X1) and competence (X2). The remaining 22.1% is influenced by other factors not described in this study.